Dimes y diretes sobre lo audiovisual en los tiempos de la cultura visual y digital - Alonso García, Luis (CIC. Cuadernos de Información y Comunicación, 2007)
The coming-up of a new domain such as Visual Studies or Visual Culture, in the art studies context, allows us to reflect upon the role played by the subject and field of Audiovisual Media in the Spanish tradition in communication studies. Anyhow the concepts of “audiovisual media” and “visual culture” refer, putting aside the presence or absence of the “audio” element, to two semantic fields which theoretically and historically have been even opposites: the first one is the media system originated by photography and telephone in the high modernity; the second one, the continuity of images in the history of Humanity. The problem of giving a strict and restricted definition of “audiovisual media” allows us, against the new studiovisualists trends, to define the contents and the limits that must have a comprehensive and complex analysis of the communication practices.